The Process of Resolving a Social Problem in the Management of City of Isfahan - Abdolmehdi Rajaee; Morteza Nooraee (تحقیقات تاریخ اجتماعی, 2012)
This article concerns with the impact of city sewage system on the lives of the people of Isfahan. On the surface it may look a superficial subject to entertain, and yet considering the importance of it with regard to the health and the impact that it has had on the mind of our forefathers, it proves otherwise. There have been various attitudes regarding the sewage of city. For centuries the sewage had been regarded as the provider of the fertilizer to the agricultural lands. Obviously collecting and carrying to the proper destination created health problems and other inconveniences which many protested. The modern view on the sewage changed. It was considered polluted remains that had to be removed without hassle. The present article compares two ways of looking at the problem of the sewage of city of Isfahan in the one and half century, which was at last was resolved through modern techniques. Also the piped water system of Isfahan that was done during that time was discussed. The question is what did the people of the cities with their sewage remains and especially the people of Isfahan what way had to deal with this problem. It is assumed that the more the modern techniques came to the help of people with regard to health, the more attempt has been made to speed up the old problems of these kinds. The research has utilized documentary data.